Out of place: fieldwork and positionality in law and society - Chua, Lynette J.; Massoud, Mark Fathi (Cambridge studies in law and society, 2024)
"This volume is a call to embrace the power of positionality, telling a new history of law and society through the experiences of successful scholars from populations that academia has historically marginalized. Experts record their positionalities across their research and document what they learned about the law in the process"--